Perancangan Gateway Sign Ikon Sekolah Wijaya Putra Dengan Metode Quality Function Deployment - Priyatna, Ridho Maudi; Riyanto, Ong Andre Wahyu (Faculty of Engineering, Wijaya Putra University, 2022)
There are many universities in Surabaya that require each university to compete, one of which is attracting prospective students and new students every year. Therefore, information and promotion media are needed to provide prospective students and new students to join. One of the promotional media used in higher education is in the form of visual communication media. Visual communication media is believed to be easy to see for the wider community. So that in this study, the author carries the theme of designing the Gateway Sign as an icon or medium of information that is easy for the public to become a gateway for directions or information media. To design the Gateway Sign product, the method used is Quality Function Deployment, which is a design method that directly involves consumers related to quality aspects. Based on the calculation of the degree of importance from the results of the average calculation of the questionnaire, the average is the largest. Gateway Sign is a public visual media that requires using an easy style of language and produces a contrast of light that does not interfere with the eyes. The last stage of the Gateway Sign product development process is an economic analysis to estimate the outlook for the product. Economic analysis uses ROI (Return of Investment) and BEP (Break-Even Point).